Family businesses and management information systems (MIS): Seven wise steps to become more electronically intelligent - Nima S. Salami (Westcliff University, 2017)
Turning a brick-and-mortar family business into an E-business, would greatly pay off, and bring every manager's dream come true, since it has the potential of creating a sustainable growth (Baltzan & Phillips, 2015). This paper will introduce the step by step guidelines for managers.